Self-assembled arrays of magnetic nanostructures on morphologically patterned semiconductor substrates - O'Dowd, Brendan (Trinity College (Dublin, Ireland). School of Physics, 2014)
This thesis deals with the formation of morphological patterns on single-crystal semi-conductor surfaces via self-assembly processes, followed by the subsequent fabrication of magnetic nanostructures whose dimensions are defined by the underlying template. Stepped surfaces on Si (Hi) were achieved by high temperature DC annealing of vicinal Si templates which causes the atomic steps to form step-bunches and/or facets. In particular, for templates annealed with the current directed in the ascending step direction it was shown that the cooling rate from the annealing temperature can be used as a precise control of step periodicity. A shallow angle deposition technique was used to create ordered rows of magnetic nanowires on the step-bunched Si templates, whose dimensions are determined by the size of the underlying steps as well as the duration and angle of deposition.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin